Interstitial incisional hernia following open appendectomy: Case report - Jude Edeh, Anthony; Uchendu, Ugochukwu Timothy; Okenwa, Wilfred Okwudili; Ilo, Chukwudi; Nwangwu, Chukwuemeka Chijioke (Indian Journal of Case Reports, 2019)
Open appendectomy is a common surgical procedure but post-appendectomy incisional hernia is uncommon, the actual incidence is probably less than 1%. The common contents of such hernias are small bowel and omentum. Primary repair of this type of hernia has a high failure rate and effective repair can be achieved by using synthetic mesh. We report a case of interstitial incisional hernia in a 70-year-old female who was presented to the hospital. She had a bulge in the the right lower quadrant of the abdomen since last 8 years. The hernia was successfully repaired by tension-free sutured prolene mesh. The follow up showed that there were no signs of reoccurrence.